Identity management policy and unlinkability: a comparative case study of the US and Germany - Rosner, Gilad L. (2014)
This study compares the privacy policies of Germany and the US in the field of identity management. It analyses the emergence of unlinkability within the countries’ electronic citizen identity initiatives. The study used qualitative research methods, including semi-structured interview and document analysis, to analyse the policy-making processes surrounding the issue of unlinkability. The study found that unlinkability is emerging in different ways in each country. Germany’s data protection and privacy regimes are more coherent than the US, and unlinkability was an incremental policy change. US unlinkability policies are a more significant departure from its data protection and policy regimes. New institutionalism is used to help explain the similarities and differences between the two countries’ policies. Scholars have long been calling for the use of privacy-enhancing technologies (PETs) in policy-making, and unlinkability falls into this category. By employing PETs in this way, German and US identity management policies are in the vanguard of their respective privacy regimes. Through these policies, the US comes closer to German and European data protection policies, doing so non-legislatively. The digital citizen identities appearing in both countries must be construed as commercial products inasmuch as official identities. Lack of attendance to the commercial properties of these identities frustrates policy goals. As national governments embark on further identity management initiatives, commercial and design imperatives, such as value to the citizen and usability, must be considered for policy to be successful.